2011
DOI: 10.1007/s13197-011-0542-6
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative effects of Brassica juncea and Moringa oliefera prepared by different processing methods

Abstract: The effects of different cooking methods (boiling, microwave cooking, frying and steaming ) on the antioxidant activity of Brassica juncea (BJ) and Moringa oliefera (MO) were assessed by measuring the total phenolic contents (TPC), total flavonoid content (TFC), DPPH radical scavenging activity and Fe 2+ -chelating ability . TPC (mg gallic acid equivalents per 100 g of dry weight) and TFC (quercetin equivalents per gram of extract) of the fresh, boiled, microwaved, fried and steamed BJ were found to be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…These data support the statement of Jaiswal and Abu-Ghannam [14] , who reported that the DPPH and FRAP scavenging capacities of York cabbage decreased at different MW powers applied. Subudhi and Bhoi [22] determined that microwave cooking reduced the DPPH and FRAP scavenging capacities of brown mustard (Brassica juncea). Contrary to it, Igual et al [58] noted a significant increase of antioxidant capacity in MW-dried apricot and suggested that the reason of increased antioxidant capacity could be due to the sampling type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support the statement of Jaiswal and Abu-Ghannam [14] , who reported that the DPPH and FRAP scavenging capacities of York cabbage decreased at different MW powers applied. Subudhi and Bhoi [22] determined that microwave cooking reduced the DPPH and FRAP scavenging capacities of brown mustard (Brassica juncea). Contrary to it, Igual et al [58] noted a significant increase of antioxidant capacity in MW-dried apricot and suggested that the reason of increased antioxidant capacity could be due to the sampling type.…”
Section: Resultsmentioning
confidence: 99%
“…Quality loss involves both of taste changes and nutrients degradation. [14,15] Many research studies have been devoted to assess the way that MW processing affects the nutrient properties of vegetables such as ready to eat vegetables [16] , broccoli [17] , green beans, broccoli, and asparagus [18] , peas, carrot, spinach, cabbage, cauliflower, and turnips [19] , potato, carrot, onion, broccoli, and white cabbage [20] , Galega kale [21] , brown mustard [22] , and York cabbage. [14] The results on the effects of MW processing on the various nutrients of vegetables reported by various authors and they differ from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Available evidence indicates that the compounds present in food supplements and medicinal plants including food fibers, vitamins, flavonoids, sterols, and other antioxidant compounds can contribute to analgesia through acting on central or peripheral nervous tissue (ZARGARI, 1997). Hydroethanolic R. communis seed extract is rich in flavonoid compounds such as quercetin, catechin, kaempferol, sinapic acid, and apigenin (SUBUDHI & BHOI, 2011). Catechin in R. communis causes suppression of inflammation through acting on and being involved in inflammatory mechanisms, exerting anti-inflammatory effects, and inhibiting the enzymes involved in this pathway such as lipoxygenase and cyclooxygenase (YESI et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[67] Boiling notably increased total polyphenol and flavonoid contents in water spinach, drumstick leaves, and Chinese mustard. [6,71,72] Accordingly, a slight increase of β-carotene after boiling was found in basil, coriander leaves, sweet potato leaves, and pak choi. [78] Similar to blanching, the increase of phytochemical compounds is likely an artifact due to the softening of the vegetable matrix due to heat, which subsequently increases extractability.…”
Section: °Cmentioning
confidence: 98%